Optimal Placement of FACTS Devices to Improve Power Flow Using Bees Algorithm - Mugiira, E.K; Ndolo, A.O (International Journal of Advanced Research in Computer Science, 2016)
Flexible AC Transmission System (FACTS) device has gained popularity recently as an essential device in power systems. The introduction of FACTS technology in power systems has seen increased flexibility and control of power flow along the transmission lines. This paper focuses on three FACTS devices namely Static VAR Compensator (SVC), Thyristor Controlled Series Capacitor (TCSC) and Unified Power Flow Controller (UPFC). The devices will be optimally placed to simultaneously minimize system real power loss and maximize the inter-tie flow using Bee Algorithm (BA). BA is a simple and efficient heuristic search method based on the foraging behavior of honey bees searching for the best food source in a recently proposed multi objective optimization algorithm. The performance of presented BA algorithm is tested and verified on the IEEE 30-bus power systems. A Genetic Algorithm (GA) configured for the same purpose is used for evaluation. Results show the difference of performance of the devices used in this situation. The results achieved in this work illustrated that BA can successfully be used to solve the nonlinear problems related to power system optimization.
Keywords: Bee algorithm; Static VAR compensator; Thyristor Controlled series compensator